Synthesis of 8, 12‐Dibromocorrole and Its Transformation to Antiaromatic 8, 10‐Fused Iminoisocorrole with a Polarized Resonance Contribution. Issue 16 (21st June 2021) - Ueta, Kento; Nakai, Akito; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract: 8, 12‐Dibromo‐5, 15‐bis(pentafluorophenyl)corrole and its Ag(III) complex were prepared via intramolecular oxidative coupling of a 8, 12‐dibromobilane precursor. The Ag(III) complex was allowed for further transformation via Suzuki coupling reaction. Thus, 2‐aminophenyl group was coupled at one of the β ‐positions, and subsequent demetalation followed by oxidation with MnO2 afforded 8, 10‐fused iminoisocorrole in good yields. The iminoisocorrole exhibited weak antiaromaticity due to the C(+)−N(−) polarized resonance contribution as evidenced by 1 H NMR spectrum, UV/vis absorption spectra, cyclic voltammetry, and theoretical calculations. Abstract : 8, 12‐Dibromocorrole was prepared via intramolecular oxidative coupling of a dibrominated bilane precursor. This synthetically useful corrole has been transformed to 8, 10‐fused iminoisocorrole, which exhibits weak yet decent antiaromatic characteristics due to the involvement of C(+)−N(−) resonance contributor.